1971
DOI: 10.3181/00379727-136-35450
|View full text |Cite
|
Sign up to set email alerts
|

Cytochalasin B II: Selective Inhibition of Cytokinesis in Xenopus laevis Eggs

Abstract: Carter (1) has described inhibition of cytoplasmic division (cytokinesis) with unimpaired nuclear division (karyokinesis) in mammalian cells treated with cytochalasin B (CB), a metabolite from the mold, Helminthosporium dematioideum. We report a similar effect of CB on the initial cleavages of Xenopus Zaevis embryos. Our data on both the duration and magnitude of drug effect define temporal limits for the act of cytokinesis and suggest that a pool of material which will be used for subsequent cleavages is avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…Treatment with critical doses of such agents led to cleavage arrest but did not completely inhibit the nuclear cycle. Although similar effects on cleavage and the nuclear cycle were described with cytochalasin B (Hammer et al, 1971), different results were obtained with anti-microtubule agents in other laboratories. For example, nuclear division was arrested, along with cleavage, following treatment with colchicine (Takeichi et al, 1985).…”
Section: Discussionmentioning
confidence: 75%
“…Treatment with critical doses of such agents led to cleavage arrest but did not completely inhibit the nuclear cycle. Although similar effects on cleavage and the nuclear cycle were described with cytochalasin B (Hammer et al, 1971), different results were obtained with anti-microtubule agents in other laboratories. For example, nuclear division was arrested, along with cleavage, following treatment with colchicine (Takeichi et al, 1985).…”
Section: Discussionmentioning
confidence: 75%
“…This is best illustrated by the studies on inhibition of cytokinesis by cytochalasin B. This is the first system where the effects of the drug were observed (32), and it has been the subject of detailed studies conducted by several investigators (12,13,33,34). There is strong evidence unrelated to cytochalasin B that the contractile ring plays an important role in the cleavage of eukaryotic cells during cell division (12,35).…”
Section: Discussionmentioning
confidence: 99%
“…In studies involving newt eggs Perry and coworkers (7) have recently demonstrated that the CR complexes with HMM, and they therefore concluded that it contains an actin-like component. Unfortunately their conclusion is not automatically applicable to contractile rings in other cells because CR microfilaments in amphibian eggs seem to be unique on two grounds: (i) they are thicker (8-10 nm) (8,9) than CR microfilaments elsewhere (4-6 nm) and (ii) whereas cytochalasin B brings about disruption of CR microfilaments in HeLa cells and sea urchin eggs (4,5), the drug elicits very little response in cleaving amphibian eggs, either in terms of inhibiting contraction or disrupting the CR (8,10,11). In this last connection, it might be reasoned that since cytochalasin B has little or no effect on native actomyosin from muscle (12)(13)(14) (Fig.…”
mentioning
confidence: 99%